Debt Recovery Management in the Banking Sector, Problems, and Prospect: A Case Study of SBI Bank in India: Challenges and Strategies in Debt Recovery Management (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Recovery of Debts and Bankruptcy Act, 1993 (RDB Act) provides speedy redressed to lenders and borrowers through filing of Original Applications (OAs) in Debts Recovery Tribunals (DRTs) and appeals in Debts Recovery Appellate Tribunals (DRATs). The sales are complete when you receive your sales proceeds, but what if sale proceeds remain outstanding or your debtor refuses to pay for credit sales. In such cases, it becomes a nightmare for an organization. This nightmare is further intensified when management needs to provide explanation every year for outstanding debtors published in your financial statements. Nowadays Debt Recovery has become the main constraint for the growth. Being the requirement of competitive business scenario, you can’t afford to avoid the sales on credit or advances. Bank customers expect their banker to provide them with loan and advance to make up for their fund also the ability for Bank to maintain adequate profitable credit policy and debts recovery technique is always maintained. Debt credit control department is not the center for banks and as such, they are mainly to charge with responsibility of making proper use of the shareholders fund for the benefit of the entire public at large.